Sex-based differences in pediatric supracondylar humerus fractures - LiBrizzi, Christa L. (Medicine (Baltimore), 2020)
Supracondylar humerus (SCH) fractures are reported to be approximately twice as common among boys as among girls. Little is known about sex-associated differences in fracture patterns and complications. We compared the incidence of pediatric SCH fractures, injury mechanism (high-energy or low-energy), fracture subtypes, associated neurologic injuries, and treatment types by patient sex. We reviewed 1231 pediatric SCH fractures treated at 1 center from 2008 to 2017, analyzing sex distributions overall and by year and fracture subtype. We noted patient demographic characteristics, injury mechanisms, neurologic injuries, and treatments (nonoperative or operative). Binomial 2-tailed, chi-squared, and Student's t tests were used for analysis. Multiple logistic regression was performed to assess associations between sex, age, and injury mechanism. Alpha = 0.05. We found no significant difference in the distribution of girls (52%) vs boys (48%) in our sample compared with a binomial distribution (P = .11). Annual percentages of fractures occurring in girls ranged from 46% to 63%, and sex distribution did not change significantly over time. The mean (± standard deviation) age at injury was significantly younger for girls (5.5 ± 2.5 years) than for boys (6.1 ± 2.5 years) (P < .001). High-energy injury mechanism was associated with older age (odds ratio [OR], 1.05; 95% confidence interval [CI], 1.03–1.06) but not male sex (OR, 1.04; 95% CI, 0.98–1.1). The overall incidence of neurologic injury was 9.5% but boys did not have greater odds of sustaining neurologic injury (OR, 1.03; 95% CI, 1.0–1.1). We found no sex-associated differences in the distribution of Gartland fracture subtypes (P = .13) or treatment type (P = .39). Compared with boys, girls sustain SCH fractures at a younger age. SCH fractures were distributed equally among girls and boys in our sample. Patient sex was not associated with fracture subtype, injury mechanism, neurologic injury, or operative treatment. These findings challenge the perception that SCH fracture is more common in boys than girls. Level III, retrospective study.